UKURAN PERUSAHAAN SEBAGAI MODERASI DALAM DETERMINASI AUDIT DELAY PADA PERUSAHAAN LQ 45 YANG TERDAFTAR DI BEI PERIODE 2016-2018 - Nesya Marciane Nadra (2020)
This study aims to determine the effect of profitability, solvency on audit delay and company size in its ability to moderate the effect of profitability and solvency on audit delay on LQ 45 companies listed on the Stock Exchange in the 2016-2018 period as a sample of research. This research is included in quantitative research with multiple linear regression analysis techniques and a special application of multiple linear namely Moderated Regression Analyz (MRA) to measure the moderating variable. The research results obtained are simultaneous profitability, solvency variables and company size moderation variables simultaneously have an effect on audit delay. While based on partial tests show that (1) profitability does not significantly influence audit delay, (2) solvency has a significant effect on audit delay, (3) company size is not able to moderate the effect of profitability on audit delay, (4) company size is able to moderate the effect of solvency to audit delay.